The role and functions of political caricature in the media - Kazykenova А. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
The article is devoted to the study of the role of political caricature as an instrument of influence on public consciousness in modern conditions of development. The concept of political caricature is considered, as well as its main functions, such as satirical, social, creative, emotive, illustrative and the function of cultural memory. The possession of the caricature by subjective and objective modality is indicated, expressing the author’s personal attitude to the events and facts being interpreted. The features of the graphic image as the main component of the caricature are considered, where the author uses a number of artistic techniques to achieve his goal, which distinguish the caricature from other types of drawings. It is noted that as the main artistic technique, cartoonists most often use exaggeration and sharpening of the characteristic features of the figure, face, costume, behavior of the depicted, as well as resort to unexpected, unusual comparisons and likenesses. Therefore, caricature is a field for the creative imagination of the artist. The essence of political caricature is indicated in the criticism of current political events, where the cartoonist sets himself the goal of intentionally expressing this or that socio-political phenomenon in a comical way, thereby influencing the formation of a certain public opinion.